Surfactin suppresses postharvest gray mold in Actinidia arguta fruit via direct antifungal activity and induced host resistance - Feiyang Wang; Sen Dong; Hang Che; Baodong Wei; Dazhi Zhang; Bingxue Li; He Gao; Shunchang Cheng (Food Control, 2027)

Partially etched Ti2AlN/Ti2N/TiN ternary composite as a synergistic catalyst for enhanced hydrogen storage kinetics and cycling stability of NaAlH4 - Chen Jin; Lingfeng Wang; Zhenke Chen; Hang Che; Shuzhong Wang; Zhiheng Liu; Tao Chen; Li Wang; Yuyuan Zhao; Xinhua Wang; Haoyuan Zheng; Haizhen Liu; et al. (Chemical Engineering Journal, 2026)

Mechanistic insights into Ti3CN MXene-modified NaAlH4: Boosting hydrogen storage kinetics and cyclability - Chen Jin; Zhenke Chen; Hang Che; Shuzhong Wang; Zhiheng Liu; Tao Chen; Li Wang; Yuyuan Zhao; Xinhua Wang; Haoyuan Zheng; Haizhen Liu; Mi Yan (Chemical Engineering Journal, 2026)

Synergistic CeH2.51/graphene nanointerface engineering for enhanced kinetics and cycling stability of Mg(NH2)2–2LiH - Chen Jin; Haoyuan Zheng; Lingfeng Wang; Zhenke Chen; Hang Che; Shuzhong Wang; Zhiheng Liu; Tao Chen; Li Wang; Yuyuan Zhao; Xinhua Wang; Haizhen Liu; et al. (Chemical Engineering Journal, 2026)

Auditory-perception-based tuneable noise control approach for improving acoustic comfort and behaviour of autistic individuals in indoor/outdoor environments - Tak Chun Kwong; Steve Wai Yin Mung; Huan-Ling Yuan; Henry Kar Hang Chu; Yuen Yi Cynthia Lai; Chetwyn Che Hin Chan; Ho Man Yu; Yat Sze Choy (Building and Environment, 2026)

Discovery and optimization of AAK1 inhibitors based on 1H-indazole scaffold for the potential treatment of SARS-CoV-2 infection - Zi Hui; Haowen Deng; Yueying Xu; Yuan Gao; Chenfeng Zhai; Nian-Dong Mao; Hao Che; Zhen Li; Yuting Zhang; Hang Zhang; Tian Xie; Xiang-Yang Ye (Molecular Diversity, 2026)

Bimetallic ion crosslinked hydrogels sequentially releasing immunomodulatory factors and osteogenic factors to promote bone integration of 3D printed titanium alloy prostheses - Xiao Sheng; Zhenjia Che; Chuncheng Shen; Jingtao Wu; Chenhao Qiu; Chenjie Tan; Junjie Mao; Bo Li; Hang Yu; Jianyou Li; Wei Liu; Chen Li; et al. (Chemical Engineering Journal, 2025)

Nitrate denitrification rate response to temperature gradient change during river bank infiltration - Yazhi Song; Xisosi Su; Qiaohui Che; Weihong Dong; Yuyu Wan; Hang Lyu; Tiejun Song (Environmental Geochemistry and Health, 2024)

Strong bacterial stochasticity and fast fungal turnover in Taihu Lake sediments, China - Shu-Hang Wang; Sheng-Wu Yuan; Fei-Fei Che; Xin Wan; Yi-Fei Wang; Dian-Hai Yang; Hai-Jiang Yang; Dong Zhu; Peng Chen (Environmental Research, 2023)

A comparative study based on performance and techno-economic analysis of different strategies for PV-Electrolyzer (green) hydrogen fueling incinerator system - Osama Majeed Butt; Muhammad Shakeel Ahmad; Teong Kai Lun; Hang Seng Che; H. Fayaz; Nasrudin Abd Rahim; Krzysztof K.K. Koziol; Neyara Radwan; Mohammad Amir Khan; Nadeem A Khan; Lakhveer Singh (Waste Management, 2023)

Contribution of five major apple polyphenols in reducing peanut protein sensitization and alleviating allergencitiy of peanut by changing allergen structure - Shanfeng Sun; Tianyi Jiang; Yanjun Gu; Lu Yao; Hang Du; Jiangzuo Luo; Huilian Che (Food Research International, 2023)

Out‐of‐Tibet: the spatio‐temporal evolution of Gentiana (Gentianaceae) - Adrien Favre; Ingo Michalak; Chih‐Hsiung Chen; Jenn‐Che Wang; James S. Pringle; Sabine Matuszak; Hang Sun; Yong‐Ming Yuan; Lena Struwe; Alexandra N. Muellner‐Riehl (Journal of Biogeography, 2016)
Aim We investigated the historical biogeography and diversification of Gentiana L. (Gentianaceae). Our study depicts the origin and dispersal routes of this alpine genus, and the role of the uplift of the Qinghai–Tibet Plateau ( QTP ) and past climate changes as triggers for its diversification. Location Tibeto‐Himalayan region and world‐wide mountain habitats. Methods Our sampling represents more than 50% of the extant Gentiana species, including all sections across their entire geographical ranges. We investigated the evolutionary history of Gentiana using phylogenetic reconstructions (maximum likelihood and Bayesian inference) of ITS , atp B– rbc L and trn L– trn F sequences, as well as molecular dating with beast . We tested two approaches of ancestral area reconstructions ( DEC , DIVA ) in BioGeo BEARS and investigated diversification rates using BAMM . Results The common ancestor of Gentiana and subtribe Gentianinae lived in the QTP region at around 34 (25–45) million years ago (Ma), and 40 (29–52) Ma respectively. From the surroundings of the QTP , Gentiana lineages dispersed to eastern China, Taiwan, Europe, North and South America, Australia and New Guinea, from mid‐Miocene onward ( c . 15 Ma–present), with only one older dispersal event to Europe ( c . 37–21 Ma). Diversification rates gradually increased over time, and two switches of diversification rates were identified in Gentianinae ( c . 7 Ma, simultaneously in the Pneumonanthe / Cruciata lineage and in Tripterospermum ). Main conclusions Gentiana existed in the QTP region throughout most of its uplift history following the India‐Asia collision. This region acted as the primary source area for dispersals to many areas of the world. Because steady increase in diversification rates coincides with the extension of the QTP , we argue that the museum theory rather than the explosive radiation theory prevails for gentians in this region, although rare shifts of diversification rates are associated with niche shifts across the alpine/subalpine ecotone.

Silver nanoparticles: partial oxidation and antibacterial activities - Chun-Nam Lok; Chi-Ming Ho; Rong Chen; Qing-Yu He; Wing-Yiu Yu; Hongzhe Sun; Paul Kwong-Hang Tam; Jen-Fu Chiu; Chi-Ming Che (JBIC Journal of Biological Inorganic Chemistry, 2007)